PENGEMBANGAN MODUL AJAR BERBASIS KURIKULUM MERDEKA PADA MATERI BENTUK ALJABAR DI KELAS VII SMP NEGERI 13 MEDAN - Endang Novi Trisna Siloto (Prodi Pendidikan Matematika FKIP Universitas HKBP Nommensen, 2023)
This study aims to obtain teaching modules based on the independent curriculum on algebraic material in class VII SMP Negeri 13 Medan that are vali, practical, and effective. The type is research used in this study is Research and Development (R&D). The teaching module development process is oriented based on the ADDIE model. The subjects in this study were all students of class VII SMP Negeri 13 Medan (chosen one class out of five classes randomly). While the object of this study is teaching material in the form of teaching modules based on the independent curriculum on algebraic material. The research instruments used in this study were validation sheets, interview, questionnaires with validation data analysis techniques, practicality and effectiveness. Based on the results of expert validation, student response questionnaries, and student assessment results, it is known that independent curriculum-based teaching modules in algebraic form material meet the very valid criteria with a percentage of 85,93%, very practical with a percentage of 86,03%, and very effective based on the results of the completeness assessment of students with a percentage of 83,33%.